2021
DOI: 10.1186/s12958-021-00790-5
|View full text |Cite
|
Sign up to set email alerts
|

5-aza-2′-deoxycitidine inhibits cell proliferation, extracellular matrix formation and Wnt/β-catenin pathway in human uterine leiomyomas

Abstract: Background Uterine leiomyoma is a benign tumor with unclear pathogenesis and inaccurate treatment. This tumor exhibits altered DNA methylation related to disease progression. DNMT inhibitors as 5-aza-2′-deoxycytidine (5-aza-CdR), have been suggested to treat tumors in which DNA methylation is altered. We aimed to evaluate whether DNA methylation reversion with 5-aza-CdR reduces cell proliferation and extracellular matrix (ECM) formation in uterine leiomyoma cells to provide a potential treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…The Wnt/β-catenin signaling pathway is a common class of signaling pathways in cancer and its activation endows cancer cells with sustained self-renewing growth properties and is associated with therapy resistance (Bugter et al, 2021). In an experiment of Carbajo-García MC et al, the findings have demonstrated that in human uterine leiomyoma primary (HULP) cells, aberrant overexpression of DNMT1 induced abnormal DNA methylation and subsequently activated the Wnt/β-catenin signaling pathway, contributing to cell proliferation and extracellular matrix (ECM) formation (Carbajo-Garcia et al, 2021). In addition, a significant Frontiers in Pharmacology frontiersin.org study on the mechanism of treatment for mantle cell lymphoma (MCL) indicated that the inactivation of the Wnt/β-catenin signaling pathway and downregulation of DNMT1 synergistically suppressed MCL, and these results could guide the dosing in the clinical treatment of MCL (Li et al, 2017).…”
Section: Regulated Mechanism Of Dnmts In the Pathogenesis Of Cancermentioning
confidence: 99%
“…The Wnt/β-catenin signaling pathway is a common class of signaling pathways in cancer and its activation endows cancer cells with sustained self-renewing growth properties and is associated with therapy resistance (Bugter et al, 2021). In an experiment of Carbajo-García MC et al, the findings have demonstrated that in human uterine leiomyoma primary (HULP) cells, aberrant overexpression of DNMT1 induced abnormal DNA methylation and subsequently activated the Wnt/β-catenin signaling pathway, contributing to cell proliferation and extracellular matrix (ECM) formation (Carbajo-Garcia et al, 2021). In addition, a significant Frontiers in Pharmacology frontiersin.org study on the mechanism of treatment for mantle cell lymphoma (MCL) indicated that the inactivation of the Wnt/β-catenin signaling pathway and downregulation of DNMT1 synergistically suppressed MCL, and these results could guide the dosing in the clinical treatment of MCL (Li et al, 2017).…”
Section: Regulated Mechanism Of Dnmts In the Pathogenesis Of Cancermentioning
confidence: 99%
“…Inhibition of DNA methylation upregulated the tumor suppressors EFEMP1 , HTATIP2 , FBLN2 , and ARHGAP10 , supporting the notion that epigenetic modification of DNA methylation is involved in the expression of tumor suppressor genes that trigger UL development. Because 5‐aza‐CdR inhibits cell proliferation, extracellular matrix formation, and Wnt/β‐catenin signaling pathway targets in HULP cells [31,41], our findings suggest that reversing DNA methylation of tumor suppressor genes could inhibit these processes. Extracellular matrix has been identified as a potential target for future therapeutics in UL [49], and we demonstrated that EFEMP2 and FBLN2 were associated with aberrant DNA methylation and that demethylation recovered their expression, suggesting potential therapeutic impact.…”
Section: Discussionmentioning
confidence: 99%
“…Human UL primary (HULP) cells obtained from individual patients ( n = 10) were isolated from UL samples as previously described [31]. To evaluate the effect of 5‐aza‐CdR on the selected downregulated and hypermethylated genes, HULP cells were treated with 0 μ m (control) or 10 μ m 5‐aza‐CdR (Abcam, Cambridge, UK) for 72 h, with the medium replaced every 24 h. Total RNA from HULP cells was obtained using a Qiagen RNeasy Mini Kit, and cDNA was synthesized using a PrimeScript RT Kit (Takara, Shiga, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate the effect of SAHA (Abcam, Cambridge, UK) on the selected downregulated and hypoacetylated genes, HULP cells were isolated from UL tissues ( n = 10) from selected women, as previously described [ 36 ] and treated with 0 μM (0.01% DMSO as a control) or 10 μM of SAHA for 48h. Then, total RNA was extracted from HULP cells using a Qiagen RNeasy Mini kit, and cDNA was synthesized using a Takara PrimeScript RT reagent kit; qRT-PCR was performed to evaluate gene expression CD40 , GIMAP8 , IL15, GPX3 and DPT in HULP cells treated with or without SAHA, as described above.…”
Section: Methodsmentioning
confidence: 99%